PENGENDALI WAKTU PENYIRAMAN PADA TANAMANHIDROPONIK MENGGUNAKAN IC 555 - Watiningsih, Tri; -, Kholistianingsih; Wahjudi, Dodi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2015)
ABSTRACT Availability of cropland is the reason why they do not want to plant crops, especially vegetables such as eggplant, cabbage, chilli, as academics eager to implement and introduce hydroponic plants so that the need for hygienic vegetables that can be realized. Along with the question, it is necessary to increase public participation for the introduction in fulfilling the need for vegetables dilahan own more hygienic through Research Lecturer Beginners "Controlling Time Watering On Plant Hidroponik Using IC 555" and utilizes cans or buckets former as cropping media so that it can implement the 3R principles in handling garbage everyday life squad in the smallest scope, Reduce minimize goods, Reuse avoid the use of disposable items, Recycle as much as possible, recycle items that are not useful anymore and converted into other goods. Technology is one of a growing breakthrough developed by the designers of automated tools as a substitute for the operation of a manual system to an automated system, all work will work automatically with an error rate that can be as small as possible. Besides, the technology is expected to automated tools human function as objects or actors on each machine. Average trying to take advantage of the narrow land yard of his house for growing plants that are useful, such as tabulapot plants, to overcome the problem of land is narrow and the provision of water, which is the working principle of the water basin is pumped into the pot plants automatically using IC 555, with the automatic watering tabulapot is expected to overcome the above problems from manual to automatic watering